Optimal controllability of 3‐composed siphons in a class of Petri nets. Issue 11 (1st May 2013) - Hou, Y.F.; Li, Z.W.; Hong, L.; Al‐Ahmari, A.M.
Abstract : A controllability condition of a siphon composed of three elementary ones in a class of Petri nets, namely S 3 PR, is developed. Under the condition, a maximally permissive liveness‐enforcing supervisor expressed by a set of monitors (control places) can be decided by an algorithm with polynomial complexity for an S 3 PR if every dependent siphon is m ‐composed with m ≤ 3.